Thymic teratoma presenting as non-immune hydrops fetalis - Hamza, Ameer; Vouyoukas, Eleftherios; Anderson, Ian Jacob; Higgins, Martha Jaye (Autopsy and Case Reports, 2018)
Teratomas are one of the most frequent tumors in the pediatric population. They occur anywhere along the midline of the body, following the course of the embryonic germ cell ridge. In the mediastinal location, they exert space occupying effects, leading to a myriad of complications, including non-immune hydrops fetalis. We describe a fatal case of an immature thymic teratoma in a neonate presenting with hydrops fetalis. This case emphasizes the importance of early diagnosis and surgical intervention in such cases.